Molecular diversity of phototrophic biofilms on building stone. Issue 2 (24th January 2013) - Hallmann, Christine; Stannek, Lorena; Fritzlar, Diana; Hause‐Reitner, Dorothea; Friedl, Thomas; Hoppert, Michael
Abstract Composition and diversity of aeroterrestrial phototrophic microbial communities are up to now poorly understood. Here, we present a comparative study addressing the composition of algal communities on sandstone substrata based upon the analysis of rRNA gene clone libraries from environmental samples and crude cultures. From a west‐facing, shaded wall area of the mediaeval castle ruin Gleichen (Thuringia, Germany), sequences mainly related to the green algae Prasiococcus and Trebouxia (Trebouxiophyceae) were retrieved. A south‐west‐facing, sun‐exposed wall area was mainly colonized by Apatococcus and a Phyllosiphon‐related alga. Just a few species, in particular Stichococcus‐related strains, were ubiquitous in both areas. Samples from a basement vault exposed to low irradiance exhibited Chlorophyceae like Chromochloris and Bracteacoccus. Thus, most green algae on the daylight‐exposed walls were affiliated to Trebouxiophyceae, whereas Chlorophyceae were dominant in samples taken from the site kept under low irradiance. Accordingly, cyanobacterial communities were different: the sun‐exposed area was dominated by Synechococcus‐related organisms, while on the shaded wall area, cyanobacteria were almost absent. The filamentous Leptolyngbya dominated samples from the basement vault. Scanning electron microscopy revealed endolithic algal morphotypes (coccoid algae and diatoms) dominant in open pores between mineral particles. Here, the organisms may be also involved in biogenic weathering of stone.